Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.17305/bjbms.2011.2593
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive analgesic effects of midazolam and diclofenac in rat model

Abstract: Th e aim of the present study was to investigate the preemptive analgesic eff ects of intraperitoneally administrated midazolam and diclofenac, before acute and infl ammatory induced pain in rat model. One hundred twenty-eight (n= in each group) male Sprague Dawley rats were included in the study. Paw movements in response to thermal stimulation or paw fl inching in response to formalin injection were compared after midazolam (., ,  and  mg/kg) and diclofenac ( mg/ kg), intraperitoneal administration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…In this context, Yano and colleagues (2006) demonstrated that, in mice, methyleugenol (10 µg/kg) isolated from Asiasari radix significantly diminished the duration of paw licking and biting time in phase 2 of the formalin test without affecting phase 1. This behavior is similar to that found in our experiments for eugenol and comparable to that produced by diclofenac, which itself has demonstrated an effect in the formalin test (Picazo, Castañeda-Hernández, Ortiz, 2006) and the thermal model of inflammation (Hasani et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…In this context, Yano and colleagues (2006) demonstrated that, in mice, methyleugenol (10 µg/kg) isolated from Asiasari radix significantly diminished the duration of paw licking and biting time in phase 2 of the formalin test without affecting phase 1. This behavior is similar to that found in our experiments for eugenol and comparable to that produced by diclofenac, which itself has demonstrated an effect in the formalin test (Picazo, Castañeda-Hernández, Ortiz, 2006) and the thermal model of inflammation (Hasani et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The doses were based on previous toxicity studies and within the normal range for testing edible plant extracts in rodent pre‐clinical studies (Mohamad Shalan et al, ). The Diclofenac dose is based on the recommended dose for rats (Hasani, Soljakova, Jakupi, & Ustalar‐Ozgen, ). Osteoarthritis (OA) were induced by intra‐articular injection of monosodium iodoacetate (MIA 3 mg in 50 μl saline) into the right knee joint (Wan Osman et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Shalan et al, 2017). The Diclofenac dose is based on the recommended dose for rats (Hasani, Soljakova, Jakupi, & Ustalar-Ozgen, 2011). Osteoarthritis (OA) were induced by intra-articular injection of monosodium iodoacetate (MIA 3 mg in 50 μl saline) into the right knee joint (Wan Osman et al, 2017).…”
Section: Animal Study For Osteoarthritismentioning
confidence: 99%
“…The Diclofenac dose is based on the reported recommended dose for rats (Hasani, Soljakova, Jakupi, & Ustalar-Ozgen, 2011). Diclofenac is the Food and Drug Administration approved drug (non-steroidal anti-inflammatory drug) for OA.…”
Section: Animal and Groupingmentioning
confidence: 99%